2020
DOI: 10.1088/1748-605x/ab5e52
|View full text |Cite
|
Sign up to set email alerts
|

Dense fibroadhesive scarring and poor blood vessel-maturation hamper the integration of implanted collagen scaffolds in an experimental model of spinal cord injury

Abstract: Severe spinal cord injury (SCI) results in permanent functional deficits, which despite pre-clinical advances, remain untreatable. Combinational approaches, including the implantation of bioengineered scaffolds are likely to promote significant tissue repair. However, this critically depends on the extent to which host tissue can integrate with the implant. In the present paper, blood vessel formation and maturation were studied within and around implanted micro-structured type-I collagen scaffolds at 10 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…implanted micro‐structured type‐I collagen scaffolds in adult rats with mid‐cervical spinal cord lateral funiculotomy injury; however, spinal cord vessels within the scaffold generally did not regenerate. [ 30 ] In this study, we observed some RECA + vessel regeneration at the lesion site where the hydrogel scaffold was implanted, which indicated that our scaffold is more conducive to the growth and regeneration of spinal cord vessels.…”
Section: Resultsmentioning
confidence: 71%
“…implanted micro‐structured type‐I collagen scaffolds in adult rats with mid‐cervical spinal cord lateral funiculotomy injury; however, spinal cord vessels within the scaffold generally did not regenerate. [ 30 ] In this study, we observed some RECA + vessel regeneration at the lesion site where the hydrogel scaffold was implanted, which indicated that our scaffold is more conducive to the growth and regeneration of spinal cord vessels.…”
Section: Resultsmentioning
confidence: 71%
“…It often leads to the formation of fibrous scarring and cystic cavity which obstructs potential neuronal ingrowth. 64,117 Proper integration between the tissue and scaffold often results in a high degree of cell infiltration to modulate the microenvironment in the lesion, given that the architectures of the scaffold are permissive to cell infiltration. 118 In addition, tissue integration is also related to supporting axonal growth by facilitating endogenous cell infiltration and migration and deposition of laminin.…”
Section: In Vivo Tissue Integration and Cell Migrationmentioning
confidence: 99%
“…More recently, it has been demonstrated that macrophages are responsible for fibroblast recruitment to the injury site and depletion of hematogenous macrophages results in reduced fibroblast density and basal lamina formation in the lesion site, and this is associated with increased axonal growth [80]. Furthermore, the proliferation of fibroblasts can induce fibrosis around biomaterial implants [81][82][83] a particular caveat of biomaterial use [84], and have been implicated in the relatively poor implant-host integration in some implanted scaffolds [65,85].…”
Section: Fibroglial Scar Formationmentioning
confidence: 99%